Associations Between Maternal Depression, Antidepressant Use During Pregnancy, and Adverse Pregnancy Outcomes: An Individual Participant Data Meta-analysis. Issue 4 (October 2021) - Vlenterie, Richelle; van Gelder, Marleen M. H. J.; Anderson, H. Ross; Andersson, Liselott; Broekman, Birit F. P.; Dubnov-Raz, Gal; El Marroun, Hanan; Ferreira, Ema; Fransson, Emma; van der Heijden, Frank M. M. A.; Holzman, Claudia B.; Kim, J. Jo; et al.
Abstract : OBJECTIVE: To evaluate the associations of depressive symptoms and antidepressant use during pregnancy with the risks of preterm birth, low birth weight, small for gestational age (SGA), and low Apgar scores. DATA SOURCES: MEDLINE, EMBASE, ClinicalTrials.gov, and PsycINFO up to June 2016. METHODS OF STUDY SELECTION: Data were sought from studies examining associations of depression, depressive symptoms, or use of antidepressants during pregnancy with gestational age, birth weight, SGA, or Apgar scores. Authors shared the raw data of their studies for incorporation into this individual participant data meta-analysis. TABULATION, INTEGRATION, AND RESULTS: We performed one-stage random-effects meta-analyses to estimate odds ratios (ORs) with 95% CIs. The 215 eligible articles resulted in 402, 375 women derived from 27 study databases. Increased risks were observed for preterm birth among women with a clinical diagnosis of depression during pregnancy irrespective of antidepressant use (OR 1.6, 95% CI 1.2–2.1) and among women with depression who did not use antidepressants (OR 2.2, 95% CI 1.7–3.0), as well as for low Apgar scores in the former (OR 1.5, 95% CI 1.3–1.7), but not the latter group. Selective serotonin reuptake inhibitor (SSRI) use was associated with preterm birth among women who used antidepressants with or without restriction to women with depressive symptoms or a diagnosis of depression (OR 1.6, 95% CI 1.0–2.5 and OR 1.9, 95% CI 1.2–2.8, respectively), as well as with low Apgar scores among women in the latter group (OR 1.7, 95% CI 1.1–2.8). CONCLUSION: Depressive symptoms or a clinical diagnosis of depression during pregnancy are associated with preterm birth and low Apgar scores, even without exposure to antidepressants. However, SSRIs may be independently associated with preterm birth and low Apgar scores. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42016035711. Abstract : Depressive symptoms or a clinical diagnosis of depression during pregnancy are associated with preterm birth and low Apgar scores, even without exposure to antidepressants.